(untitled) (University of Khartoum Engineering Journal, 2022)
Many types of grids are developed to address the fast growing demand such as smart grid and Microgrid. The main objectives of this paper were to explore the implementation of Microgrid in a fish farm, to show the benefit of adding a renewable source; the photovoltaic system. The Micro-grid consisted of old Indian diesel pumps- which caused all types of pollution diesel spill engine oil spill, noise and utility supply. Photovoltaic system is added after a catastrophic accident by contamination a fish pond by mix of diesel and engine oil killing tens of thousands of fishes. The Photovoltaic system panel was connected directly to a DC centrifugal solar pump. The solar pump produced an average flow rate of 0.0073 m3/s (210.65 m3 per day). The data sheet showed that the selected pump should produce 200 m3 per day, and this means that the design performance and experiment results are in close agreement. Furthermore, this grid shows a good actual experience of using solar pump for fish ponds as replacement of the traditional diesel-based method.